Implementasi Kebijakan Penyederhanaan Organisasi Di Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi - Irfan Setiawan; Rahmawati Sururama; Ismail Nurdin (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
The implementation of government organization requires a lean and flexible bureaucracy to provide quality and non-rigid public services. The research aims to analyse the steps in simplifying government organization and implementing simplification of organizational structures in Minister of Administrative and Bureaucratic Reform. The method used in this research is qualitative descriptive by collecting data through interviews, observations, and documentations according to the theme studied. The result shows that the steps conducted by the Minister comprises regulatory preparation activities, arrangement for position map formations and socialization to all employees in the minister environment. In implementing of simplifying the organization in Minister of Administrative and Bureaucratic Reform, well-implemented policy are produced from food communications, adequate resources, well-conducted disposition, and available bureaucratic reform.